Risk factors for spinal cord lesions in dystonic cerebral palsy and generalised dystonia. Issue 2 (29th September 2011) - Guettard, Emilie; Ricard, Damien; Roze, Emmanuel; Elbaz, Alexis; Anheim, Mathieu; Thobois, Stéphane; Lepeintre, Jean-Francois; Galanaud, Damien; Mazel, Christian; Vidailhet, Marie
Abstract : Background: Cervical myelopathy (CM) in patients with cerebral palsy (CP) is underdiagnosed as symptoms of spinal cord lesions, being similar to those due to dystonia, may be overlooked or identified late. The aim of this study is to identify the risk factors and clinical characteristics of CM in patients with generalised dystonia, including dystonic CP. Methods: The authors conducted a case–control study to identify early clinical signs of CM in consecutive patients with generalised dystonia. The authors compared the clinical characteristics and symptoms of those who developed CM (cases) and those who did not (controls). The same clinical information on possible neurological manifestations of CM was collected for cases and controls at the date of the last visit. Results: Out of 54 patients, 17 (31%) developed symptomatic CM during the study period. In all cases, CM occurred after the age of 36 years. 81% of cases and 35% of controls had a Burke–Fahn–Marsden movement subscore for the neck >4. Age (OR per 10 years=2.3, 95% CI 1.4 to 4.2, p=0.006) and severity of neck dystonia (OR=7.7, 95% CI 1.7 to 49.6, p=0.005) were the main risk factors of CM. Gait disorders and falls, wasting of hand muscles and bladder disorders were the best clinical clues of CM. Conclusions: As severity of cervical dystonia and age are the major risk factors for spinal cord lesions, dystonic patients, including patients with dystonic CP, should be screened for CM from the third decade of life onwards. Early recognition of CM is crucial for functional prognosis and impact on autonomy.